Heat acclimation does not reduce the impact of hyperthermia on central fatigue - Brazaitis, M.; Skurvydas, A. (European Journal of Applied Physiology, 2010)
We tested the hypothesis that improved physiological symptoms of passively induced heat acclimation (HA) might impair the impact of hyperthermia on central fatigue and consequently cause greater peripheral fatigue. Subjects in the experimental group (7 males and 6 females) completed seven sessions of HA involving passive heating of the lower body by immersion up to the waist in a water bath at ~44°C (air T 23°C, rh 40%) for 45 min, repeated every other day for 2 weeks. During the first and the last HA sessions, participants performed a 2-min MVC of the knee extensors. A TT100 Hz was superimposed on the contraction at about 3, 14, 29, 44, 59, 74, 89, 104, and 119 s. At about 30, 60, 90, and 120 s, the knee extensors were relaxed for 2-3 s and a control TT100 Hz was delivered. The participants in the control group (6 males and 6 females) followed the same exercise protocol on days 1 and 14 in a thermoneutral condition. Peak torque and the muscle voluntary activation and half-relaxation time were assessed during the exercise. The attainment of HA was confirmed by significant decreases in the resting and final rectal temperatures (~0.3°C), heart rate, and physiological stress index, and increased sweating capacity. Lower-body heating resulted in greater central and peripheral fatigue when compared with the thermoneutral condition during the 2-min MVC. Following HA, central and peripheral fatigues were unchanged. We conclude that passively induced HA for 2 weeks improved the physiological symptoms, but did not change central or peripheral fatigue during exercise in hyperthermia.